Biais de genre dans la reconnaissance des maladies professionnelles : l’exemple des troubles musculosquelettiques (TMS) en Italie et en Suisse - Isabelle Probst; Silvana Salerno (Perspectives Interdisciplinaires sur le Travail et la Santé)
Background. More knowledge of gender inequalities in occupational health, particularly those related with the insurance system, is necessary for prevention. Objectives. Describe the role of gender differences in the recognition and declaration of musculoskeletal disorders (MSD) as occupational diseases in two countries, Switzerland and Italy. Data Sources. Statistics of the Swiss and Italian occupational health insurance systems. Results. A lower recognition rate of musculoskeletal disorders in women was found in both countries. This result is primarily explained by each country’s compensation system. In Italy, it was mainly due to the list of occupational diseases, and in Switzerland, case law and the interpretation of scientific data. Discussion. Gender inequalities in the recognition of musculoskeletal work-related diseases are confirmed as has been already shown in other countries (Canada and Belgium). Gender-oriented national statistical data and their monitoring by both Italy and Switzerland would foster preventive actions.